The Role of Teacher Quality in Improving the Competitiveness of Educational Institutions in the Era of Global Transformation at MTs Nahdlatul Muslimin Undaan Kudus - Sania Kumala; Sukarman; Muhammad Khoiruddin (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
Global transformation requires educational institutions to continuously adapt and improve their competitiveness. One of the strategic factors in building institutional competitiveness is the quality of teachers as the spearhead of the educational process. This study uses a descriptive qualitative approach, Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman model. The results of the study show that teacher quality is the most dominant factor in building the competitiveness of educational institutions at MTs Nahdlatul Muslimin Undaan Kudus. In the context of Undaan Subdistrict, Kudus Regency, there are at least five secondary educational institutions competing with each other to attract public interest. The improving of quality teachers at MTs Nahdlatul Muslimin was carried out through three main strategies: (1) improving academic qualifications through master's degree scholarships, (2) conducting regular seminars and training as a form of continuing education, and (3) providing compensation and appropriate rewards for outstanding teachers. These three strategies contribute significantly to improving teachers' pedagogical, professional, social, and personal competencies. Improving teacher quality has a direct impact on the quality of learning, student achievement, and the reputation of the institution in Undaan.